The impact of work demand on work-family conflict: a case study at the Kuala Muda District Police Headquarters (IPD), Kedah / Nik Nazihah Wan Mohd Fauzi and Rozila Mat Rasid - Wan Mohd Fauzi, Nik Nazihah; Mat Rasid, Rozila (2010)
When individuals perceive that the demand of the work exceed their ability to cope with both work and family, thereby a stressful condition occurs which endangers the employee’s well-being. Work-family conflict will contribute to negative work attitude, increased absenteeism, increased turnover, decreased performance, poorer physical and mental health while work-family conflict can be defined as a form of interrole conflict in which the role pressures from the work and family domains are mutually incompatible in some respect. The objectives of this research are to investigate the impact of hours worked of the employees on work-family conflict, to identify the relationship between impacts of work schedule inflexibility with level of work-family conflict and to examine the work stressors which contribute the most to work-family conflict. The type of work demand that has been studied in this research are hours worked, work schedule inflexibility and work stressors. The total respondents of 159 staffs of the Kuala Muda Distict Police Headquarters (IPD), Kedah were selected through convenience sampling where the respondents were selected randomly. The questionnaires were distributed to the respondents which consists of five sections such as demographic (Section A), work-family conflict (Section B), hours worked (Section C), work schedule inflexibility (Section D) and work stressors (Section E). The data was analyzed using Descriptive Statistics, Pearson Correlation, Cronbach’s Alpha and Multiple Regression Analysis of Statistical Package for Social Sciences (SPSS) version 16.0.